Habenaria trichosantha Lindl.: A newly recorded orchid from China - ZHAO Mingxu; WANG Hengying; TAN Yunhong; SUN Xingxu; HU Xingrun; CHEN Fei (Xibei zhiwu xuebao)
[Objective] This paper reports the first occurrence of Habenaria trichosantha Lindl. (Orchidaceae) in China. Detailed anatomic photos at blooming period are provided and the differences with its morphologically close relatives are summarized. [Methods] Morphological observation of wild population plants of this species in China was carried out, and the main taxonomic features were photographed and recorded. [Results] H . trichosantha Lindl. was only recorded in the Eastern Himalayas and Indo-China Peninsula historically. It is found in the Savanna ecosystem of the dry-hot valley of Nujiang in western Yunnan. The most recognizable feature of its flower is the fan-shaped outline of the lateral lobe of the lip, which is divided into long tassels with secondary branches. Thus, it is easily distinguished from other species of the same genus. [Conclusion] H . trichosantha Lindl. is a newly recorded species in China, which further enriches the resources of wild orchids in China.